Epidemiological and clinical aspects of a sample of Brazilian patients with primary dystonia and the impact of the new classification on their clinical evaluation - Torben Cavalcante Bezerra; Nathália Novaretti; Ana Luiza Nunes Cunha; Márcio Alexandre Pena Pereira; Daniel Sabino de Oliveira; Manuelina Capelari Marcuz Brito; Ângela Vieira Pimentel; Vitor Tumas (Arquivos de Neuro-Psiquiatria)
ABSTRACT Dystonia is a relatively common movement disorder but some of its epidemiological and clinical aspects have not been well characterized in Brazilian patients. Also, a new clinical classification for the disorder has been proposed and its impact on clinical practice is unclear. We aimed to describe the clinical and demographic characteristics of a Brazilian series of patients with primary dystonia, to estimate its local prevalence, and to explore the impact of using a new classification for dystonia. We identified 289 patients with primary dystonia over a 12-month period, of whom235 underwent a detailed evaluation. Patients with primary dystoniamade up one-sixth of all patients evaluated at the service where the study was conducted, with an estimated local prevalence of 19.8/100,000 inhabitants. The clinical and demographic characteristics of the patients were similar to those described elsewhere, with blepharospasm as the most common focal dystonia and most patients using sensory tricks that they judged useful on a day-to-day basis. The application of the new classification was easy and simple, and the systematic approach allowed for a better clinical characterization of our patients. We recognized two dystonic syndromes that were not described in the original article that proposed the classification, and suspected that the arbitrary distinction between generalized and multifocal dystonia seems not to be useful for patients with primary dystonia. In conclusion, the prevalence and clinical characteristics of our patients were not distinct from other studies and the new classification was shown to be practical and useful to characterize patients with dystonia.